Measurement properties of generic preference-based measures in individuals with chronic obstructive pulmonary disease - Mehdipour, Ava (My University, 2020)
Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. Luckily, many interventions are available for patients with COPD to improve their symptoms and exercise tolerance, and reduce exacerbation events. Generic preference-based measures are measures of health-related quality of life that can be used for cost-utility analysis. However, before these measures can be used to make healthcare decisions, their psychometric properties (i.e., reliability, validity, responsiveness) have to be assessed. The aim of this thesis was to evaluate the psychometric properties of generic preference-based measures in people with COPD. First, a systematic review was conducted to evaluate the existing evidence on the psychometric properties of these measures in people with COPD. Then, a content validation study was conducted to examine whether these measures accurately reflect the areas of life important to people with COPD. Findings from these two studies showed that generic preference-based measures were not sensitive or fully reflective of patients’ health concerns. Findings highlighted the need for properly designed studies (e.g., using correct methodology) when evaluating the psychometric properties of generic preference-based measures in COPD. In addition, our results suggest the need for development of a COPD-specific preference-based measure to improve the sensitivity of cost-utility analyses in this population. This in turn would enable the health-related quality of life of individuals with COPD to be accurately captured when making healthcare decisions.